2021
DOI: 10.1172/jci127171
|View full text |Cite
|
Sign up to set email alerts
|

MIF but not MIF-2 recruits inflammatory macrophages in an experimental polymicrobial sepsis model

Abstract: Authorship note: PVT and WS contributed equally to this work. Conflict of interest: RB and JB are listed as co-inventors on issued patents (US20120149044A1 and US20100267714A1) for MIF antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 59 publications
1
42
1
Order By: Relevance
“…Studies have shown that after LPS stimulated macrophages, rapamycin target protein, and hypoxia inducible factor-1 α (hypoxia-inducible factor-1 α , HIF-1 α ). Increased expression can promote the expression of glycolysis-related genes and increase the expression of fructose-2-kinase 6-phosphate, thereby promoting aerobic glycolysis [ 18 ]. After LPS activated macrophages, the expression of inducible nitric oxide synthase increased, and the activity of some target proteins in mitochondrial electron transport chain.…”
Section: Changes Of Macrophages In Sepsismentioning
confidence: 99%
“…Studies have shown that after LPS stimulated macrophages, rapamycin target protein, and hypoxia inducible factor-1 α (hypoxia-inducible factor-1 α , HIF-1 α ). Increased expression can promote the expression of glycolysis-related genes and increase the expression of fructose-2-kinase 6-phosphate, thereby promoting aerobic glycolysis [ 18 ]. After LPS activated macrophages, the expression of inducible nitric oxide synthase increased, and the activity of some target proteins in mitochondrial electron transport chain.…”
Section: Changes Of Macrophages In Sepsismentioning
confidence: 99%
“…We found that MIF-(CD44-CD74) pairs mediated signaling from CD4 + T cells and CD8 + T cells to macrophage-like VSMCs. On the other hand, MIF-(CD74 + CXCR4) mediated signal transmission from contractile VSMCs, T-cell-like VSMCs, and macrophage-like VSMCs to B cells Numerous studies have shown that MIF possesses the function of recruiting and activating macrophages through combining with CD74 and CXCR2 (24)(25)(26) and promote normal cells to acquire an inflammatory phenotype by interacting with the receptor CD74 (27). MIF binds to CD74 + CXCR4, which promotes B-cell migration (28).…”
Section: Discussionmentioning
confidence: 99%
“…88 In contrast, Rajasekaran and colleagues found that MIF-2 promotes the recruitment of neutrophils into inflamed lungs. 105 While the role of CXCR2, an established neutrophil recruitment chemokine receptor, was not specifically explored in that study, the observed lack of involvement of CXCR2 in the macrophage recruitment experiments of Tilstam et al 88 may suggest that MIF-2mediated neutrophil recruitment may be supported by a CD74 and/or CXCR4 mechanism, or via an indirect mechanism, as implicated by Schindler et al, who obtained evidence for monocyte/macrophage-neutrophil crosstalk. 103 Winner et al revealed a covalent modification at the Nterminal proline of both MIF-2 and MIF by 4-IPP, which leads to the production of 6-phenylpyrimidine (6-PP) adduct.…”
Section: Mif-2 In Acute Inflammation Sepsis and Covid-19 And Comparis...mentioning
confidence: 95%
“…58 At the same time, chemotactic effects elicited by MIF-2 are unlikely to involve CXCR2 engagement. 88 Morphometric plaque analysis suggests that Mif-2 knockout mice exhibit reduced lesions and plaque macrophage counts in both early and advanced stages of atherosclerosis. The latter also implies that MIF-2-elicited lesional leukocyte recruitment promotes atherogenesis.…”
Section: Role Of Mif-2 In Heart Failure and Comparison To Mifmentioning
confidence: 99%
See 1 more Smart Citation